Importation of yellow fever into China: assessing travel patterns - Wilder-Smith, Annelies; Leong, Wei Yee (Journal of travel medicine, 2017)
Abstract. Rapid increase in trade and a growing air passenger market encourages high travel volume between the regions associated with increasing risks of such